Contents and Forms in Conceptions, Presentations and Interpretations of Opposites and Contradictions - Jože Krašovec (Bogoslovni Vestnik, 2023)
The article deals with the complex perception of opposites in the order of the phenomenal world and different interpretations of opposites and contradictions in philosophy, in Biblical studies and in theology. The ways of perception and directions of interpretation of opposites and contradictions at the level of the material world show that most people do not perceive opposites as contradictions, but as different parts of the whole cosmic reality. The common direction of interpretation is inclusive and therefore complementary. In mental and spiritual perception of life situations and of the state of morality the situation is different. The more we perceive life spiritually, the more we encounter polarization between inclusive and exclusive directions of interpretation of contrasting reality. Presentations of reality in the world of literature are perceived in two ways: one way is the inclusive polar expression of the entirety of the laws of reality through the use of opposite words, concepts, phrases and discourses; the second way is the exclusive perception of opposites as contradictions between the morally acceptable and unacceptable. The purpose of the article is to determine how levels of education, aspects of cosmic and supercosmic, transcendent reality, and ideological orientations influence the actually adequate or inadequate or mistaken perception of the role of opposites in the order of the material world and in the order of morals and values. The analysis of literary types and genres and the style of biblical texts is a particularly rich field of perception and expression of opposites and contradictions: polar opposites in support of realism in life, contradictions in condemnation of deceptive and arbitrary interpretations that do not correspond to the material and moral design of the world and life in it. Truth and lies are not polarly inclusive, but antithetically exclusive concepts which, according to biblical revelation, can only serve for a polar, i.e. complementary, perception of the whole of reality in a contingent world. In the announcement of the last judgment, there is such a complete contrast between them that the lie is abolished by itself and by the judgment of absolute Godʼs holiness.